Durability and Failure Types of S2-Alar-Iliac Screws: An Analysis of 312 Consecutive Screws. (18th November 2021) - Hyun, Seung-Jae; Jung, Jong-myung; Kim, Ki-Jeong; Jahng, Tae-Ahn
Graphical Abstract: